Fluid loading in abdominal surgery - saline versus hydroxyethyl starch (FLASH Trial): study protocol for a randomized controlled trial. Issue 1 (December 2015) - Futier, Emmanuel; Biais, Matthieu; Godet, Thomas; Bernard, Lise; Rolhion, Christine; Bourdier, Justine; Morand, Dominique; Pereira, Bruno; Jaber, Samir
Abstract Background Inappropriate fluid therapy during surgery is associated with significant morbidity and mortality. Few studies have examined the effects of particular types of fluids (crystalloid or colloid solutions) in surgical patients, especially with the goal of hemodynamic optimization. Isotonic saline is the most commonly used fluid worldwide but may be associated with potential nephrotoxicity. Hydroxyethyl starch (HES) solutions are widely used in surgical patients as a component of goal-directed fluid optimization strategies, but several large multicenter studies have suggested increased rates of acute kidney injury and adverse events with the use of HES in ICU patients. Despite what may be inferred from physiological studies, the benefit and harm of 0.9 % saline and HES during hemodynamic therapy have not been clearly established in surgical patients. Methods/Design The FLASH trial is an investigator-initiated, prospective, multicenter, randomized, double-blinded, two-arm trial, randomizing 826 patients with moderate-to-high risk of postoperative complications to receive 6 % HES 130/0.4 or 0.9 % saline during individualized goal-directed fluid optimization. The primary outcome measure is a composite of death or major postoperative complications within 14 days following surgery. The sample size will allow the detection of a 10 % absolute between-group difference in the primary outcome measure with a type 1 error rate of 5 % and power of 95 %, assuming a 5 % mortality rate and 20 % morbidity (thus 25 % for the composite endpoint). Discussion The FLASH trial may provide important data on the efficacy and safety of commonly used fluid solutions and could have a significant impact on future treatment of surgical patients. Trial registration ClinicalTrials.gov Identifier:NCT02502773 . Registered 16 June 2015.